Development of integrated seaweed culture and capture fisheries in Indonesia. Issue 1 (September 2020) - Najamuddin,; Hajar, M A I; Rustam,; Palo, M; Asni, A
Abstract: Seaweed development has had positive impacts on surrounding environments and fisheries resources, even using traditional technologies. The integration of aquaculture and capture fisheries will have a multiplier effect on fish farmer income as well as supporting the development of the aquaculture sector. This research aimed to optimize the utilization of fisheries resources around seaweed culture areas. Two case studies were conducted at Libukang Island, Jeneponto District, South Sulawesi, and at Sarudu village, North Mamuju District, West Sulawesi. Resource use in seaweed culture areas was optimized through the design, construction, and implementation of improved fishing gears: gill nets, bamboo traps, and fyke nets. The study results show that integrating seaweed culture and capture fisheries using these gears can increase fishermen's incomes. The level of additional income depends on fishing intensity. In addition, seaweed culture productivity should be improved through integration with fish cage culture. The cultured fish expel waste to the environment (feed, feces, and urine) that can provide nutrients to the seaweed. The sustainability of fishing depends so much on the sustainability of seaweed culture were used as a fish aggregating device.